2023
DOI: 10.1029/2023gb007798
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variability of the Surface Ocean Carbon Cycle: A Synthesis

Keith B. Rodgers,
Jörg Schwinger,
Andrea J. Fassbender
et al.

Abstract: The seasonal cycle is the dominant mode of variability in the air‐sea CO2 flux in most regions of the global ocean, yet discrepancies between different seasonality estimates are rather large. As part of the Regional Carbon Cycle Assessment and Processes phase 2 project (RECCAP2), we synthesize surface ocean pCO2 and air‐sea CO2 flux seasonality from models and observation‐based estimates, focusing on both a present‐day climatology and decadal changes between the 1980s and 2010s. Four main findings emerge: Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 134 publications
1
16
0
Order By: Relevance
“…Although differences in the biogeochemistry in the models may cause the discrepancy, there is insufficient observational data available to evaluate this. A similar discrepancy in the seasonal cycle of p CO 2w between the products and the models has been found in the global ocean (Rogers et al., 2023).…”
Section: Discussionsupporting
confidence: 76%
“…Although differences in the biogeochemistry in the models may cause the discrepancy, there is insufficient observational data available to evaluate this. A similar discrepancy in the seasonal cycle of p CO 2w between the products and the models has been found in the global ocean (Rogers et al., 2023).…”
Section: Discussionsupporting
confidence: 76%
“…However, the coarse spatial resolution and lack of seasonal variability and biological carbon cycling in the OCIM could still bias its estimates of F ant,CO2 . Seasonality is known to influence rates of anthropogenic CO 2 uptake (Rodgers et al, 2008), and this variability will become more important as the ocean acidifies and the Revelle buffer factor increases, enhancing the biologically and temperature-driven seasonal variations in seawater chemistry (Fassbender et al, 2018(Fassbender et al, , 2022Hauck & Völker, 2015;Rodgers et al, 2023). The influence of missing seasonality, small-scale circulation features, and biology on anthropogenic CO 2 uptake by the OCIM has not been quantified, but here we adopt an ad hoc estimate of about 10%-15%, or an additional 0.3 PgC yr −1 uncertainty to the OCIM estimates of F ant,CO2 .…”
Section: Additional Uncertainties and Biases In Estimates Of The Glob...mentioning
confidence: 99%
“…Furthermore, a study with ESMs has shown that AMOC-biases are strongly correlated to sea surface temperature biases in the North Atlantic (Wang et al, 2014). While we did not analyze sea surface temperature biases in the North Atlantic, Rodgers et al (2023) found that the seasonal cycle of pCO 2 in the subpolar Atlantic is thermally driven in the GOBMs while that of the pCO 2 -products is non-thermally driven. This might lead to the F net of the GOBMs being more sensitive to warming than that based on pCO 2 products (Goris et al, 2018), which may contribute to the increasing gap between GOBMs and pCO 2 -products with time.…”
Section: Journal Of Advances In Modeling Earth Systemsmentioning
confidence: 70%